2011
DOI: 10.1007/s11033-011-1147-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of 5′ regulatory region of ovine FSHR gene and its association with litter size in Small Tail Han sheep

Abstract: Single nucleotide polymorphisms of 5' regulatory region of follicle-stimulating hormone receptor (FSHR) gene were detected in two high prolificacy sheep breeds (Small Tail Han and Hu sheep) and two low prolificacy sheep breeds (Corriedale and Chinese Merino sheep) by polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP). The results indicated that there were three genotypes (AA, AB and BB) detected by primer 1 in Hu sheep while only one genotype (AA) in other three sheep breeds, and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…At present, IGF1 (He et al, 2012), FSHR (Chu et al, 2012a), KISS-1/GPR54 (Chu et al, 2012b), PPNR (Guan et al, 2011), INHBB (Chu et al, 2011a) and BMPR-IB (Chu et al, 2011b) have been identified as candidate genes affecting Hu sheep fecundity. However, until now, no gene with a major effect on reproduction has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…At present, IGF1 (He et al, 2012), FSHR (Chu et al, 2012a), KISS-1/GPR54 (Chu et al, 2012b), PPNR (Guan et al, 2011), INHBB (Chu et al, 2011a) and BMPR-IB (Chu et al, 2011b) have been identified as candidate genes affecting Hu sheep fecundity. However, until now, no gene with a major effect on reproduction has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the SNP G-29A in the 5'-upstream region of the FSHR gene has been detected in both women with primary and secondary amenorrhea in India (Achrekar et al, 2010) and infertile men in Southeast Turkey (Balkan et al, 2010). In goats, five mutations (C-93A, G-80C, C-63A, C-56G, and T-55C) have been identified in Xiangdong Black, Nanjiang Brown and Guizhou Black goats (Zhu et al, 2007), two SNPs (C-629T and T-681C) in Hu sheep, and three novel SNPs (G-200A, G-197A and T-98C) in Small Tail Han sheep in the 5'-upstream region of the FSHR gene (Chu et al, 2012), where these mutations are significantly associated with litter size traits. SNP G-278A was found in Chinese Holstein cows in our previous study (Yang et al, 2010), and also detected in Luxi cattle in this study.…”
Section: Polymorphisms Of 5'-flanking Region Of the Fshr Genementioning
confidence: 99%
“…Due to the important roles of FSH in follicular growth and ovarian steroidogenesis in females, mutations in the FSHR gene could affect reproductive ability. So far, a large number of mutations have been detected in the FSHR gene, which are associated with reproductive diseases in humans such as polycystic ovary syndrome (Whitney et al, 1995;Conway et al, 1999), ovarian dysgenesis, secondary amenorrhea, or partial FSH resistance syndrome (Beau et al, 1998;Touraine et al, 1999), and superovulation response in cows (Yang et al, 2010), as well as litter size in Small Tail Han sheep (Chu et al, 2012). However, whether the FSHR polymorphism has any effect on pregnancy rate is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Marker selection is an important trend in practical genetics (Marker Assisted Selection -MAS), suggesting the use of DNA markers associated with productivity traits [3,4]. The DNA marker-based technologies are widely applied in national breeding programs in several countries with developed sheep breeding [5,6].…”
Section: Introductionmentioning
confidence: 99%